PATH-20. COMPREHENSIVE GENOMIC PROFILING COMPARING PRIMARY CNS LYMPHOMA TO SYSTEMIC DIFFUSE LARGE B CELL LYMPHOMA REVEALS BIOMARKERS INDICATING POTENTIAL BENEFIT FROM IMMUNE CHECKPOINT INHIBITORS. (6th November 2017) - Severson, Eric; Vergilio, Jo-Anne; Gay, Laurie; Daniel, Sugganth; Elvin, Julia; Suh, James; Covert, Mandy; Brown, Charlotte; Miller, Vincent; Stephens, Philip; Ross, Jeffrey; Ramkissoon, Shakti
Abstract: BACKGROUND: B-Cell Primary CNS Lymphoma (PCL) is Diffuse Large B-cell Lymphoma (DLBCL) confined to the CNS. Less than 50% of PCL patients achieve complete remission with current therapies. Comprehensive genomic profiling (CGP) may suggest novel treatment modalities including use of immune checkpoint inhibitors (ICPI). DESIGN: 24 cases of B-cell PCL and 432 cases of DLBCL were evaluated by CGP of 405 genes via DNAseq for all classes of genomic alterations and 265 genes via RNAseq for fusions (FoundationOne Heme). Tumor mutational burden (TMB) was calculated from 1.23 Mb of sequenced DNA. RESULTS: The PCL cohort was 50% male and 50% female, aged 21 to 84 with a median age of 66, while the DLBCL cohort was 64% male and 36% female, aged 14 to 88 with a median age of 63. Genomic alterations with significant differences between PCL and DLBCL included MYD88 (50.0% vs 17.6%), ETV6 (38% vs 2.3%), PIM1 (25.0% vs 7.6%), PRDM1 (25.0% vs 5.8%), CXCR4 (16.7% vs 2.5%), TP53 (16.7% vs 40.3%), and CREBBP (0.0% vs 21.5%) (p<0.05 by two-tailed Fisher Exact Test). Median TMB was similar (median 9.2 vs 10 mutations/mb) and the percent of TMB-high cases (>20 mutations/mb) were not statistically different (33% vs 19%). Two PCL cases were PD-L1 ( CD274 ) amplified with TMBs of 64 and 10 mutations/mb. CONCLUSIONS: CGP of PCLs reveals biomarkers predictive of ICPI efficacy including TMB-high (33%) and CD274 amplification (8%). These results could be used to refer patients to clinical trials such as NCT02779101 employing ICPI treatment in PCL. This is the first series of PCL to report mutational burden and demonstrate a significantly increased frequency of ETV6, CXCR4 and PIM1 genomic alterations in comparison to DLBCL. Given the limitations of standard of care for PCL, CGP can potentially identify new therapeutic approaches in this rare form of lymphoma.